YOUTH CENTER DENGAN PENDEKATAN ARSITEKTUR REGIONALISME DI KABUPATEN MAGELANG - Risya Agus Arifah; Edi Pramono Singgih; Marsudi Marsudi (ARSITEKTURA, 2015)
Designing Youth Center in Magelang Regency, motivated by positive environmental needs of adolescents, especially in Magelang Regency which currently didn’t have a special space to carry out various activities such as sports, arts and skills, as well as the potential and achievements of young people in Magelang Regency in the field of sport and art  have not received guidance. The purpose of  this architectural planing is to provide a place for the youth in Magelang Regency wich can accomodate recreation, socializing, innovate, and develop talent, so that they can have wholesome recreational facility that can develop their interests and talents as well as socializing ability wich will bring the better changes. The approach used in determining the design is by using the concept of Regionalism Architecture which is applied in form and fasade building as well as the pattern of mass arrangement. The result obtained is the design of a training and recreation facilities for young people that is Youth Center in Magelang Regency with Regionalism Architecture approach, wich can visible in the use of Borobudur Temple elements, such as stone material, stone step pyramid structure landscape arragement, centrally balanced composition, application of Borobudur Temple ornamens, The main building floor plan wich has a form that resembles Borobudur Temple floor plan, as well as the shape of a pyramid roof wich is the application form from Borobudur Temple stupa.  Keywords:Adolescent, Borobudur Temple, Fasade Building. Regionalism Architecture, Youth Center, Youth Facility.